The Perceptions of UPI's Student About Halal Certified Gastronomical Restaurants - Helvy Siti Zahra Fitriyadi; Anne Nuraini; Masya Hasna (Universitas Airlangga, 2022)
Halal certificates are important for Muslims in general. However, because we are in a Muslim-majority country of Indonesia, sometimes halal certification in restaurants is often forgotten. This is because the possibility of restaurants that produce non-halal products is very small because there are not as many enthusiasts as halal products. The purpose of this study is to find out the views of UPI students about gastronomic restaurants that have not been certified halal. The method used is qualitative with a descriptive approach with data collection in the form of questionnaires. It consists of 7 questions regarding related titles, with a total of 35 respondents. Although there are non-Muslim respondents, some people agree that there is a halal certificate at a restaurant. However, it is possible that some argue that halal certificates are not very important in Indonesia, which is majority Muslim, automatically the raw materials for products will adjust to the largest market. Keywords: Gastronomi, restoran, halal